Double-plasma metal synergistic metal organic framework composite SERS (Surface Enhanced Raman Scattering) substrate as well as preparation method and application thereof in diazepam detection
By constructing the Ag@ZIF-8@Au composite SERS substrate, the problems of expensive instruments when detecting diazepam residue in aquatic products in the prior art are solved, and the instrument is expensive, cumbersome pre-processing, high detection cost and poor sensitivity are achieved, and a fast and sensitive detection effect is achieved.
Patent Information
- Application Number
- CN202411896504.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art has problems such as expensive instruments, cumbersome pre-processing, high detection cost and poor sensitivity when detecting diazepam residues in aquatic products, making it difficult to achieve fast and sensitive detection.
A double plasma metal synergistic metal organic frame composite SERS substrate Ag@ZIF-8@Au was used to construct a core-shell-shaped highly sensitive SERS sensor by layer-by-layer assembly of wet chemistry to detect diazepam residues.
Fast and sensitive detection of diazepam residues is achieved, with the detection limit as low as 0.126ng/mL, and the detection linear range is wide. The detection process can be completed within 10 minutes, reducing the detection cost.
Smart Images

Figure CN119595612A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of drug detection, and in particular relates to a dual plasma metal-synergistic metal-organic framework composite SERS substrate, a preparation method thereof, and an application thereof in detecting diazepam. Background Art
[0002] In order to maintain the freshness of aquatic products, diazepam is widely used to slow down the metabolism of aquatic animals and reduce their stress response. This application has played a certain role in preventing agitation and damage during transportation. However, diazepam (DZP) is a typical benzodiazepine. The World Health Organization's International Agency for Research on Cancer has classified benzodiazepines as Class III carcinogens. Drug-dependent zoster drugs (BDZs) have been used worldwide as sedatives, anxiolytics, and hypnotics. Their depressant effects on the central nervous system (CNS) have led to their frequent use in epilepsy treatment, as they are able to suppress the seizure state and prevent epileptic seizures.
[0003] Diazepam is frequently detected in aquatic environments due to high rates of misuse, overdose, or careless disposal, as well as its persistence in the environment. Moreover, these drugs present challenges in terms of degradation in wastewater treatment plants. For example, diazepam concentrations up to 850 ng / L were measured in surface water collected from 258 rivers in 104 countries. Residual concentrations of diazepam in industrial wastewaters were as high as 25.9 μg / L, while concentrations in surface water near wastewater outfalls were 9.5 μg / L. However, diazepam residues in aquatic products have the potential to accumulate in the human body through the food chain. The adverse consequences of the use of these drugs in the short and long term are well documented. These include symptoms such as fatigue, limb dysfunction, and mental confusion. In addition, there are reports of drug dependence and rebound effects, especially sleep disturbances after drug withdrawal. It is particularly noteworthy that according to the National Food Safety Standard - Maximum Residue Limits of Veterinary Drugs in Food (GB 31650-2019), diazepam should not be detected in animal-derived foods. Similarly, according to the Maximum Residue Limits of Veterinary Drugs in Animal-derived Foods (Ministry of Agriculture and Rural Affairs Announcement No. 235), diazepam is not allowed to be detected in animal-derived foods.
[0004] At present, the main detection methods for diazepam in aquatic products mainly rely on liquid chromatography-mass spectrometry (LC-MS / MS), gas chromatography-mass spectrometry (GC-MS) and high performance liquid chromatography-electrospray ionization-tandem mass spectrometry (HPLC-ESI-MS / MS). These methods have shown remarkable sensitivity and accuracy. However, their sample pretreatment procedures are not only time-consuming, but also very cumbersome and complicated. In addition, due to the large investment in instruments and equipment and the need for highly professional personnel to operate, the associated detection costs are also very high. In addition to the above-mentioned traditional detection methods, there are also electrochemical detection methods. The electrochemical method is characterized by high sensitivity and fast detection speed; however, it requires a dedicated workstation and electrodes. Moreover, it also has shortcomings in detection specificity and stability, so there are some limitations in practical applications.
[0005] In summary, in view of the serious harm of diazepam residues to human health and the shortcomings of existing detection methods, such as expensive instruments, cumbersome and time-consuming sample pretreatment and extensive training before sample analysis, high detection limit, short linear range and poor sensitivity, it is urgent to establish a stable and efficient detection method. This new detection method should be able to achieve rapid and sensitive identification of diazepam residues in aquatic products, reduce the detection limit, and expand the linear detection range, thereby playing a positive role in improving the quality of aquatic products. Summary of the invention
[0006] The invention provides a dual plasma metal-coordinated metal-organic framework composite SERS substrate, wherein the SERS substrate is Ag@ZIF-8@Au.
[0007] The above Ag@ZIF-8@Au was prepared by the following method:
[0008] The Ag@ZIF-8 solution and the AuNPs solution were mixed, stirred vigorously, and then allowed to react. After the reaction was completed, Ag@ZIF-8@Au was obtained.
[0009] In the above-mentioned preparation method of Ag@ZIF-8@Au, the volume ratio of the Ag@ZIF-8 solution to the AuNPs solution is selected from 1:(1-4); preferably 1:2.
[0010] In the above-mentioned preparation method of Ag@ZIF-8@Au, the time of the vigorous stirring is selected from 1 to 10 minutes, preferably 5 minutes.
[0011] In the above-mentioned preparation method of Ag@ZIF-8@Au, the static reaction time is selected from 0.5 to 2 hours, preferably 1 hour.
[0012] The above Ag@ZIF-8 solution was prepared by the following method:
[0013] Zn(NO3)2·6H2O and dimethylimidazole were mixed and dissolved in solvent A, and AgNPs solution was added. The reaction was stirred and allowed to stand. The reaction solution was centrifuged and the precipitate was washed to obtain Ag@ZIF-8. Ag@ZIF-8 was dispersed in solvent B to obtain Ag@ZIF-8 solution.
[0014] In the above-mentioned method for preparing the Ag@ZIF-8 solution, each raw material is selected from the following parts:
[0015] 100-300 parts of Zn(NO3)2·6H2O, 10-100 parts of dimethylimidazole, 50-100 parts of solvent A, 1-10 parts of AgNPs solution, and 1-10 parts of solvent B; wherein both solvent A and solvent B are methanol;
[0016] When the component is a solid component, the portion number represents milligrams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0017] In a specific embodiment, each raw material is selected from the following parts:
[0018] 207.9 parts of Zn(NO3)2·6H2O, 57.4 parts of dimethylimidazole, 80 parts of solvent A, 5 parts of AgNPs solution, and 5 parts of solvent B; wherein both solvent A and solvent B are methanol;
[0019] When the component is a solid component, the portion number represents milligrams; when the component is a liquid component, the portion number represents milliliters; in actual applications, the portion number can be enlarged or reduced in proportion to the portion number.
[0020] In the above-mentioned method for preparing the Ag@ZIF-8 solution, the stirring reaction conditions are selected from: stirring at 5-20° C. for 1-5 h; preferably: stirring at 15° C. for 3 h.
[0021] In the preparation method of the Ag@ZIF-8 solution, the standing condition is selected from: standing at 20-40° C. for 5-15 hours; preferably: standing at room temperature for 12 hours.
[0022] The above AgNPs solution was prepared by the following method:
[0023] 0.17g AgNO3 and 0.11g PVP were dissolved in 50mL water to obtain a mixed AgNO3 solution. 0.44g AA was added to 5mL water to obtain an AA solution. Then, 5mL of the mixed AgNO3 solution was added to a beaker containing 44mL water, and stirred continuously for 10min under a magnetic stirrer, followed by rapid addition of 0.2mL AA solution and 1.8mL water. After 10min of reaction, the reaction product was centrifugally washed with ultrapure water and anhydrous ethanol for 10min, and this step was repeated 3 times to remove impurities and obtain AgNPs. AgNPs were dispersed in 10mL methanol to obtain an AgNPs solution.
[0024] The AuNPs solution was prepared by the following method:
[0025] Mix 0.25mL HAuCl4 and 7.5mL CTAB, then add 0.6mL ice-cold NaBH4 solution under magnetic stirring, and react for 1 minute to obtain a gold seed solution, which is stored at room temperature for 1 hour. The prepared gold seed solution is diluted 10 times for later use; 6.4mL CTAB solution is mixed with 0.8mL HAuCl4 solution, and 3.8mL AA solution, 32mL water and 20μL diluted gold seed solution are added in sequence; after standing for 4 hours, wash three times with ultrapure water by centrifugation, and then dissolve with 8mL methanol to obtain AuNPs solution.
[0026] In the above-mentioned method for preparing AuNPs, the concentration of HAuCl4 is 0.01M, the concentration of CTAB is 0.1M, the concentration of NaBH4 solution is 0.01M, and the concentration of AA solution is 0.1M.
[0027] The present invention provides the use of the above-mentioned Ag@ZIF-8@Au in the detection of diazepam residues; preferably, the present invention provides the use of the above-mentioned Ag@ZIF-8@Au in the detection of diazepam residues in food; the food can be selected from aquatic products such as fish, shrimp, crab, etc.
[0028] The present invention provides a method for detecting diazepam residues in food, the steps of which are as follows:
[0029] 15 μL of Ag@ZIF-8@Au was transferred to the silicon wafer and dried naturally. Then, 15 μL of Ag@ZIF-8@Au was added to the silicon wafer again and waited for natural drying. 15 μL of the sample solution to be tested was added to the dried silicon wafer and placed in a vacuum drying oven at 60°C for 10 min. After drying, SERS detection was performed. If diazepam was present in the sample to be tested, the sample solution at 1076 cm -1 、1180cm -1 、1582cm -1If diazepam does not exist in the sample to be tested, its Raman characteristic peak will not appear.
[0030] In the above detection method, the Raman parameters of the SERS detection are set as follows: laser wavelength is 532nm, power is 3.1MW, integration time is 0.01s, 10 accumulations, and objective lens is 10×.
[0031] In the above detection method, the sample to be tested can be prepared by the following method (according to the pre-treatment steps of the national standard):
[0032] Take 2g of the sample, grind it into small pieces, homogenize it, and use it as a sample for further use. Dissolve 2g of the sample in a centrifuge tube with 20mL of acetonitrile, and then ultrasonicate it in a water bath for 5 minutes. Then, centrifuge the sample solution at 4000r / min for 10min, and place the obtained supernatant in a chicken heart bottle. Then, rotary evaporate the supernatant to nearly 5mL at 50℃ and mix it with 7.5mL of n-hexane. Finally, blow the lower layer solution to 1mL in nitrogen at 50℃, then dilute it to 4mL with deionized water, mix it well and set aside.
[0033] The beneficial effects of the present invention are:
[0034] The present invention adopts a layer-by-layer assembly wet chemical method and uses dual plasma metals (Ag, Au) combined with metal organic framework materials (ZIF-8) to construct a core-shell high-sensitivity SERS sensor (Ag@ZIF-8@Au). The SERS substrate can be used for sensitive and efficient detection of diazepam, with a detection limit as low as 0.126 ng / mL and a wide detection linear range of 10 -2 ~10 -9 g / mL.
[0035] The SERS sensor prepared by the present invention has the characteristics of good dispersibility and multiple hot spot effects. The gold-silver composite metal provides a stronger Raman enhancement effect, and the surface plasma resonance of the gold and silver nanoparticles can be coupled through the localized surface plasmon phenomenon. This resonance coupling effect will lead to an enhancement of the electromagnetic field between the metal structures, which can achieve a stronger localized surface enhancement effect and help improve the detection sensitivity and resolution of the nanostructure.
[0036] ZIF-8 controls the distance between AgNPs and AuNPs to obtain dense hot spots, which is beneficial to the Raman enhancement effect. Embedding MOF into precious metal materials can achieve analyte enrichment and Raman signal amplification at the same time.
[0037] The present invention utilizes the organic metal framework ZIF-8 to greatly improve the specific surface area and adsorption performance of the SERS substrate. As a porous coordination polymer, ZIF-8 can provide a large specific surface area for nanoparticles, cover the surface of the nanostructure, and increase the number of molecules adsorbed. It can achieve efficient adsorption of diazepam in the target solution, greatly improve the sensitivity of the SERS sensor, and expand the linear detection range.
[0038] The preparation method of the dual plasma metal-coordinated metal-organic framework composite substrate of the present invention is simple, the required materials are common medicines and reagents, the required instruments are common test instruments, and the cost is low.
[0039] The present invention utilizes a SERS substrate based on Ag@ZIF-8@Au, so that the process of detecting diazepam can be completed within 10 minutes. Compared with traditional detection methods, the workflow time is greatly shortened. The SERS substrate provides a new idea for the rapid and sensitive detection of diazepam.
[0040] The SERS sensor of the present invention has good sensitivity, uniformity, reproducibility and storage stability. The SERS enhancement factor of the prepared Ag@ZIF-8@Au platform is 1.128×10 6 , the RSD value in the uniformity and reproducibility experiments was as low as 10.05%, and the Ag@ZIF-8@Au substrate still retained 86.86% of the SERS activity after storage for 42 days, with an RSD value as low as 4.93%.
[0041] In summary, the SERS sensor prepared by the present invention has good application prospects and value in the field of drug residue detection technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Characterization of the relevant materials in Example 1; wherein, a is the SEM image of AgNPs; b is the SEM image of Ag@ZIF-8; c is the SEM image of Ag@ZIF-8@Au; d is the HAADF-STEM image of Ag@ZIF-8@Au; e is the SEM image of Ag@ZIF-8@Au; f is the TEM image of Ag@ZIF-8@Au; g is the TEM image of Ag@ZIF-8@Au; h is; i~l are TEM-EDS images of Ag@ZIF-8@Au;
[0043] Figure 2 UV spectrum (a), FT-IR spectrum (b), XRD pattern (c), and Raman spectrum (d) of each material;
[0044] Figure 3 Surface enhanced Raman spectra of R6G at different concentrations;
[0045] Figure 4 The Raman spectra of the homogeneity and reproducibility test (a) and 20 random points of R6G at 617 cm -1 、1359cm -1 、1512cm -1 RSD diagram of SERS characteristic peak intensity (b~d);
[0046] Figure 5 R6G at 617cm under different storage days -1 The intensity of the Raman characteristic peak at
[0047] Figure 6 Surface enhanced Raman spectra of diazepam at different concentrations (a) and standard curve (b);
[0048] Figure 7 are optimization experiments; a and b are the shell thickness optimization experiments of ZIF-8; c and d are the AuNPs size optimization experiments; e and f are the volume ratio optimization experiments of Ag@ZIF-8 and AuNPs. DETAILED DESCRIPTION
[0049] In the present invention, polyvinyl pyrrolidone is abbreviated as PVP, ascorbic acid is abbreviated as AA, and cetyl trimethyl ammonium bromide is abbreviated as CTAB.
[0050] Other materials used in the present invention, unless otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only intended to illustrate the present invention, and are not intended to limit the scope of the present invention in any way.
[0051] Example 1
[0052] The steps for preparing the dual-plasmon metal-synergistic metal-organic framework composite SERS substrate are as follows:
[0053] (1) Preparation of AgNPs
[0054] 0.17g AgNO3 and 0.11g PVP were dissolved in 50mL ultrapure water to obtain an AgNO3 mixed solution. 0.44g AA was added to 5mL ultrapure water to obtain an AA solution. Then, 5mL of the AgNO3 mixed solution was added to a beaker containing 44mL ultrapure water, stirred continuously for 10min under a magnetic stirrer, and then 0.2mL of AA solution and 1.8mL of ultrapure water were quickly added. Then, the color of the solution changed from colorless to gray-black, indicating that a large amount of silver nanoparticles were formed. After 10min of reaction, the reaction product was centrifuged and washed with ultrapure water and anhydrous ethanol for 10min, and this step was repeated 3 times to remove impurities and obtain AgNPs. Finally, AgNPs were dispersed in 10mL of methanol to obtain an AgNPs solution.
[0055] (2) Synthesis of Ag@ZIF-8
[0056] 207.9 mg Zn(NO3)2·6H2O and 57.4 mg dimethylimidazole were mixed and dissolved in 80 mL methanol, and 5 mL AgNPs solution was added. Stir at 15 °C for 3 h, and then stand at room temperature for 12 h. After that, the product was centrifuged for 10 min, and the precipitate was washed with ultrapure water to obtain Ag@ZIF-8. Ag@ZIF-8 was dispersed in 5 mL methanol to obtain Ag@ZIF-8 solution.
[0057] (3) Preparation of AuNPs
[0058] Mix 0.25 mL HAuCl4 (0.01 M) and 7.5 mL CTAB (0.1 M) in a beaker, then add 0.6 mL ice-cold NaBH4 solution (0.01 M) under magnetic stirring. After reacting for 1 min, a gold seed solution is obtained, which is stored at room temperature for 1 h. The prepared gold seed solution is diluted 10 times for later use.
[0059] 6.4 mL of CTAB solution (0.1 M) was mixed with 0.8 mL of HAuCl4 solution (0.01 M), and 3.8 mL of AA solution (0.1 M), 32 mL of ultrapure water, and 20 μL of the diluted gold seed solution were added in sequence. After standing for 4 h, the mixture was centrifuged and washed three times with ultrapure water to obtain AuNPs. AuNPs were dissolved in 8 mL of methanol to obtain an AuNPs solution.
[0060] (4) Synthesis of Ag@ZIF-8@Au
[0061] 1 mL of Ag@ZIF-8 solution was mixed with 2 mL of AuNPs solution in a volume ratio of 1:2, stirred vigorously for 5 min, and allowed to react for 1 h to obtain Ag@ZIF-8@Au solution.
[0062] The above materials are characterized as follows:
[0063] The scanning electron microscopy (SEM) images of the AgNPs are shown in Figure 2. Figure 1 a. Scanning electron microscope images show that silver nanoparticles are roughly spherical with an average diameter of about 150 nm.
[0064] Zeolitic imidazolate framework-8 (ZIF-8) is a typical metal-organic framework (MOF) composed of M-IM-M units, where M and IM represent metal cations (such as zinc (II) ions) and imidazolate linkers (such as 2-methylimidazole), respectively. Figure 1 As shown in (b), a thick ZIF-8 shell is grown around the silver nanoparticles to form Ag@ZIF-8 submicron-sized truncated rhombic dodecahedrons (TRDs). Obviously, the addition of ZIF-8 can increase the specific surface area of the substrate, which is beneficial to the adsorption of target molecules.
[0065] After adding the prepared gold nanoparticles, Ag@ZIF-8@Au was formed. The smaller gold nanoparticles can be evenly embedded in the porous surface of ZIF-8, forming a core-shell structure similar to lychee. The scanning electron microscope image is shown in Figure 1 In c and 1e, transmission electron microscopy (TEM) images show Figure 1 f and 1g. At the same time, Figure 1 h~ Figure 1 As shown in Figure 1, the transmission electron microscopy-energy dispersive spectroscopy (TEM-EDS) elemental image further confirmed the successful synthesis of Ag@ZIF-8@Au.
[0066] The UV absorption spectrum shows that the prepared AgNPS has a strong absorption characteristic band at 487nm, and ZIF-8 has an absorption peak at 227nm. After ZIF-8 is deposited on AgNPs, due to the interaction between Ag and ZIF-8, the surrounding dielectric medium changes and intermolecular resonance are caused, and the absorption peak of Ag@ZIF-8NRs blue-shifts to around 479nm, and the characteristic absorption peak of ZIF-8 also disappears. Figure 2 As shown in a, the ultraviolet absorption peak of Au NPs has a strong absorption characteristic band at 565nm. Compared with Ag@ZIF-8 and Ag@ZIF-8@Au, the absorption peak of Ag@ZIF-8@Au appears to be red-shifted from 479 to 583nm, which can be attributed to the local surface plasmon coupling effect of AgNPs and AuNPs.
[0067] FT-IR spectroscopy further confirmed the structural composition of Ag@ZIF-8@Au. Figure 2As shown in (b), the crystal structures of Ag@ZIF-8 and Ag@ZIF-8@Au were characterized. Compared with Ag@ZIF-8, the position of the characteristic peaks of Ag@ZIF-8@Au did not change, indicating that the crystal structure of ZIF-8 was well preserved and was not affected by Ag or Au nanoparticles. However, Ag@ZIF-8@Au and gold nanoparticles showed lower infrared transmittance. This is because the gold element has good light absorption properties and a high refractive index in the infrared band, which causes the infrared light to be reflected and absorbed on the gold layer and is not easy to penetrate. In addition, all the characteristic peaks of Ag@ZIF-8@Au are consistent with those of ZIF-8. The stretching vibration of CN in 2-methylimidazole appears at 1586cm -1 3136cm -1 and 2929cm -1 The peak at 1453cm belongs to the CH bond. -1 、1425cm -1 and 1308cm -1 The peak at 1145cm belongs to the stretching and bending vibration of the imidazole ring. -1 The strong peaks at 994 cm-1 and 757 cm-1 correspond to the CN stretching mode. -1 and 689cm -1 Corresponding to the deformation vibration and out-of-plane bending vibration of C=CH.
[0068] The purity and crystal structure of Ag, Ag@ZIF-8 and Ag@ZIF-8@Au were studied by XRD instrument. Figure 2 As shown in Figure c, the XRD spectrum of silver nanoparticles shows diffraction peaks at 38.2nm, 44.4nm, 64.6nm and 77.5nm, which are attributed to the (111), (200), (220) and (311) crystal planes of Ag. There are no interference peaks in the XRD spectrum of Ag, indicating that the purity of Ag is high. For the Ag@ZIF-8 sample, the diffraction peaks at 7.3°, 10.4°, 12.7°, 14.7°, 16.4° and 18.0° belong to the (011), (002), (112), (022), (013) and (222) crystal planes of ZIF-8, respectively. The diffraction peaks of Ag@ZIF-8@Au are the same as those of Ag@ZIF-8, and the peak intensities at 38.2°, 44.4°, 64.6° and 77.5° are increased, which may be due to the overlap of the peaks of gold and silver. The diffraction peaks of ZIF-8 and gold and silver nanoparticles can be clearly distinguished, which means that ZIF-8 and noble metal nanoparticles maintain a high degree of crystallinity in the composite matrix. The high crystallinity and structural integrity of Ag@ZIF-8@Au confirm the formation of Ag@ZIF-8@Au.
[0069] In order to explore the effect of SERS enhancement, the present invention collected the Raman spectra of Ag NPs, Ag@ZIF-8 and Ag@ZIF-8@Au substrates using diazepam as the signal molecule. Figure 2 As shown in Figure d, Ag NPs, Ag@ZIF-8, and Ag@ZIF-8@Au all show Raman peaks of different intensities. The SERS intensity of Ag@ZIF-8 at the characteristic peak of diazepam is significantly higher than that of Ag NPs, indicating that ZIF-8 has excellent molecular adsorption capacity, and the "hot spots" formed by core-shell nanoparticles have a stronger LSPR effect, showing a good SERS enhancement effect. In addition, for Ag@ZIF-8@Au, the SERS intensity of the characteristic peak of diazepam is about 3 times that of Ag@ZIF-8NPs, indicating that the plasma coupling of the Au-Ag composite bimetallic exhibits a stronger Raman enhancement effect.
[0070] Example 2
[0071] Physical properties study:
[0072] Rhodamine 6G (R6G) was used as a beacon molecule to investigate the sensitivity, uniformity, reproducibility and storage stability of Ag@ZIF-8@Au as a SERS substrate.
[0073] The Raman parameters in all the following experimental steps were set as follows: laser wavelength of 532 nm, power of 3.1 MW, integration time of 0.01 s, 10 accumulations, objective lens of 10×. The instrument used was a microscopic Raman imaging spectrometer.
[0074] 1. Sensitivity
[0075] 15 μL of Ag@ZIF-8@Au methanol solution (Ag@ZIF-8@Au solution prepared in Example 1) was transferred to the silicon wafer using a pipette. After natural drying, 15 μL of Ag@ZIF-8@Au was added dropwise to the silicon wafer again and allowed to dry naturally. -4 ~10 -8 M) 15 μL of the standard aqueous solution was dripped onto the dried silicon wafer, which was placed in a vacuum drying oven at 60°C for 10 minutes before SERS detection. The surface enhanced Raman spectra of R6G at different concentrations are shown in Figure 2. Figure 3 shown. Figure 3 The SERS signal response of Ag@ZIF-8@Au to different concentrations of R6G shows that with the increase of R6G concentration (10 -4 ~10 -8 M), 1359cm -1 The characteristic peak intensity of R6G at the position increases. After calculation, the SERS enhancement factor of the SERS substrate for R6G is 1.531×10 6This shows that Ag@ZIF-8@Au has a strong enhancement effect as a Raman enhancement substrate and has high detection sensitivity.
[0076] 2. Homogeneity and reproducibility
[0077] The above method was used to detect the 10 -5 SERS signal of M R6G. Five points were randomly selected for SERS detection in each sample, and the Raman spectra obtained were as follows: Figure 4 The experimental results show that the RSD of the SERS characteristic peak intensity of R6G from different groups and 20 random points is 617cm -1 12.01%, 1359cm -1 10.05%, 1512cm -1 is 14.68% (such as Figure 4 b~ Figure 4 d), demonstrating that Ag@ZIF-8@Au has good uniformity and reproducibility.
[0078] 3. Storage stability
[0079] The Ag@ZIF-8@Au methanol solution prepared in Example 1 was stored at 4°C for 42 days. During this period, 30 μL of the Ag@ZIF-8@Au methanol solution was taken every 7 days to detect 10 -6 M SERS signal of R6G. R6G at 617cm under different storage days -1 The Raman characteristic peak intensity at Figure 5 The experimental results show that after 42 days of storage, the Ag@ZIF-8@Au substrate still retains 81% of its SERS activity, proving that the Ag@ZIF-8@Au substrate has good stability.
[0080] Example 3
[0081] Diazepam test:
[0082] Using Ag@ZIF-8@Au as SERS substrate to detect different concentrations of DZP (10 -2 ~10 -9 g / mL).
[0083] 15 μL of Ag@ZIF-8@Au methanol solution (Ag@ZIF-8@Au solution prepared in Example 1) was transferred to the silicon wafer using a pipette. After natural drying, 15 μL of Ag@ZIF-8@Au was added dropwise to the silicon wafer again and allowed to dry naturally. -2 ~10 -915 μL of a 100 μg / mL (400 μg / mL) standard methanol solution was dripped onto the dried silicon wafer and SERS detection was performed after it was naturally dried.
[0084] The test results are as follows Figure 6 As shown:
[0085] like Figure 6 As shown in a, the SERS intensity increases with the increase of DZP concentration. DZP at 1076 cm -1 、1180cm -1 and 1582cm -1 There is an obvious Raman characteristic peak at 1076cm -1 The peak at 1180cm is the ring breathing vibration; -1 The peak at 1582cm is the CCC stretching vibration; and -1 The strongest characteristic peak at 1582 cm corresponds to the stretching vibration caused by C=N. In addition, in order to explore the SERS performance of Ag@ZIF-8@Au sensor for quantitative detection of DZP, the -1 The peak at was used to establish a standard curve between the logarithmic concentration (g / mL) and the intensity of DZP, as shown in Figure 6 As shown in b, y = 495.16x + 4942.64, the linear detection range of DZP is 10 -2 ~10 -9 g / mL, the absolute coefficient reaches R 2 =0.9953, and the detection limit is as low as 0.126 ng / mL.
[0086] Application Example 1
[0087] Diazepam in fish, shrimp and crab was detected using Ag@ZIF-8@Au as SERS substrate.
[0088] 1. Fish
[0089] (1) Sample preparation
[0090] Take 2g of fresh fish meat, grind it into small pieces, and homogenize it as a sample for further use. Dissolve 2g of the sample in a centrifuge tube with 20mL of acetonitrile, and then ultrasonicate it in a water bath for 5 minutes. Then, centrifuge the sample solution at 4000r / min for 10min, and place the obtained supernatant in a chicken heart bottle. Then, rotary evaporate the supernatant to nearly 5mL at 50°C and mix it with 7.5mL of n-hexane. Finally, blow the lower layer solution to 1mL in nitrogen at 50°C, then dilute it to 4mL with deionized water, mix well and set aside. Different amounts of diazepam were added to obtain concentrations of 5×10 -3 g / mL, 5×10 -5 g / mL and 5×10 -7g / mL of DZP sample solution to be tested.
[0091] (2) SERS detection
[0092] Take 15 μL of Ag@ZIF-8@Au methanol solution (Ag@ZIF-8@Au solution prepared in Example 1) and transfer it to the silicon wafer. After natural drying, add 15 μL of Ag@ZIF-8@Au to the silicon wafer again and wait for natural drying. Add 15 μL of the above diazepam solution to be tested to the dried silicon wafer, place it in a vacuum drying oven at 60°C, dry for 10 minutes, and perform SERS detection after drying.
[0093] The Raman parameters in the above experimental steps were set as follows: laser wavelength was 532 nm, power was 3.1 MW, integration time was 0.01 s, accumulation was 10 times, and objective lens was 10×.
[0094] 2. Shrimp
[0095] The sample preparation process was the same as above. The concentrations of diazepam in shrimp samples were 5×10 -3 g / mL, 5×10 -5 g / mL and 5×10 -7 g / mL. The SERS detection process is the same as above.
[0096] 3. Crabs
[0097] The sample preparation process was the same as above. The concentrations of diazepam in crab samples were 5×10 -3 g / mL, 5×10 -5 g / mL and 5×10 -7 g / mL. The SERS detection process is the same as above.
[0098] The test results are shown in Table 1:
[0099] Table 1 Detection of diazepam in samples
[0100]
[0101] The results of the fish meat test showed that the amount of diazepam added was 5×10 -3 g / mL, the recovery rate was 111.9% and the RSD was 5.00%; the amount of diazepam added was 5×10 -5 g / mL, the recovery rate was 106.7% and the RSD was 9.35%; the amount of diazepam added was 5×10 -7 g / mL, the recovery was 93.9% and the RSD was 3.82%.
[0102] The shrimp meat test results showed that the amount of diazepam added was 5×10 -3g / mL, the recovery rate was 96.2% and the RSD was 4.20%; the amount of diazepam added was 5×10 -5 g / mL, the recovery rate was 105.6% and the RSD was 7.15%; the amount of diazepam added was 5×10 -7 g / mL, the recovery was 87.2% and the RSD was 2.80%.
[0103] The crab test results showed that the amount of diazepam added was 5×10 -3 g / mL, the recovery rate was 85.9% and the RSD was 3.96%; the amount of diazepam added was 5×10 -5 g / mL, the recovery rate was 85.3% and the RSD was 2.39%; the amount of diazepam added was 5×10 -7 g / mL, the recovery rate was 94.8% and the RSD was 8.22%.
[0104] The above results show that using the Ag@ZIF-8@Au prepared in the present invention as the SERS substrate can accurately detect diazepam in fish, shrimp and crab.
[0105] Optimization Example 1
[0106] 1. ZIF-8 shell thickness optimization experiment
[0107] The addition amount of 2-methylimidazole and Zn(NO3)2·6H2O was used as the only variable (the molar ratio of the two was always 1:1), the total volume of each material was half of that in Example 1, and the other experimental steps and parameters were the same as in Example 1. In the process of synthesizing the ZIF-8 shell, the addition amount of the precursors was 0.1mmol, 0.2mmol, 0.35mmol, 0.5mmol and 0.7mmol, respectively, that is, the addition amount of 2-methylimidazole was 8.2mg, 16.4mg, 28.7mg, 41.0mg and 57.4mg, respectively, and the addition amount of Zn(NO3)2·6H2O was 29.7mg, 59.4mg, 103.95mg, 148.5mg, and 207.9mg, respectively. -5 M) is a beacon molecule, and the specific experimental steps are the same as those in Example 2. The Raman properties of the five products obtained are tested.
[0108] The test results are as follows Figure 7 a and Figure 7 As shown in b:
[0109] The Raman intensity of R6G increases first and then decreases, and based on Ag@ZIF-8@Au, the addition amount of ZIF-8 of 0.35mmol shows the best Raman enhancement. Although a high concentration of ZIF-8 helps to adsorb enough target molecules, the excess ZIF-8 in Ag@ZIF-8@Au will lead to an increase in the distance between AgNPs and AuNPs, leaving a weak electromagnetic field intensity. In summary, in the preparation process of ZIF-8 shell, the addition amount of both precursors is preferably 0.35mmol.
[0110] 2. AuNPs size optimization experiment
[0111] The size of gold nanoparticles was controlled by changing the amount of gold seed solution added, with the amount of gold seed solution added (0 μL, 10 μL, 20 μL, 30 μL, 40 μL) as the only variable, and the other experimental steps and parameters were the same as in Example 1. The obtained product was subjected to SERS detection. SERS detection was performed on R6G (1×10 -5 M) is the target molecule, and the specific experimental steps are the same as those in Example 2.
[0112] The test results are as follows Figure 7 c and Figure 7 d:
[0113] As the amount of gold seed solution added increases, the SERS activity of Ag@ZIF-8@Au gradually increases and then decreases. When the Au seed volume is low, the SERS activity of the Ag@ZIF-8@Au platform increases with the increase of the Au seed volume and reaches a maximum when the Au seed volume is 20 μL. These results indicate that AuNPs of appropriate size are advantageous to obtain superior Sers performance. It is observed that a higher amount of Au seeds is not conducive to further increase in the Sers activity of the Ag@ZIF-8@Au platform. When the Au seed volume exceeds 20 μL, the SERS intensity of the probe molecule decreases sharply. Due to the increase in the gold seed volume, the number of gold particles on Ag@ZIF-8@Au gradually increases. When the gold seed volume reaches 40 μL, the size of the Au nanoparticles increases and the distribution becomes sparse, resulting in a decrease in the number of hot spots and a decrease in the Raman intensity. Therefore, the optimal gold seed addition amount for the Ag@ZIF-8@Au platform is 20 μL.
[0114] 3. Optimization experiment of volume ratio of Ag@ZIF-8 and AuNPs
[0115] Ag@ZIF-8@Au was prepared by controlling the different volume ratios of Ag@ZIF-8 and Au NPs, with different volume ratios of Ag@ZIF-8 and AuNPs (1:1, 1:2, 1:3, 1:4, i.e., 1 mL:1 mL, 1 mL:2 mL, 1 mL:3 mL, 1 mL:4 mL) as the only variable, and other experimental steps and parameters were the same as those in Example 1. The obtained product was subjected to SERS detection. SERS detection was performed with R6G (1×10 -5 M) is the target molecule, and the specific experimental steps are the same as those in Example 2.
[0116] The experimental results are as follows Figure 7 e and Figure 7 f:
[0117] It can be clearly observed that the best SERS performance is obtained at a volume ratio of 1:2. Adding a certain amount of gold nanoparticles in the preparation of Ag@ZIF-8@Au nanoparticles can increase the number of hot spots in the gap between AgNPs and AuNPs. However, the enhancement of the Raman effect depends not only on the hot spot area in the gap between AgNPs and AuNPs, but also on the absorption of ZIF-8 and the gap between adjacent AuNPs. Once there are too many AuNPs on the surface of Ag@ZIF-8 nanoparticles, the gap between adjacent AuNPs will decrease, thereby reducing the electromagnetic field intensity and the absorption of ZIF-8. In summary, the optimal volume ratio of Ag@ZIF-8 and AuNPs is 1:2.
[0118] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A dual-plasma metal-synergistic metal-organic framework composite SERS substrate, characterized in that: The SERS substrate is Ag@ZIF-8@Au.
2. The SERS substrate according to claim 1, characterized in that: The Ag@ZIF-8@Au was prepared by the following method: The Ag@ZIF-8 solution and the AuNPs solution were mixed, stirred vigorously, and then allowed to react. After the reaction was completed, Ag@ZIF-8@Au was obtained.
3. The SERS substrate according to claim 2, characterized in that: The volume ratio of the Ag@ZIF-8 solution to the AuNPs solution is selected from 1:(1-4); and / or the time of the vigorous stirring is selected from 1-10 min; and / or the time of the static reaction is selected from 0.5-2 h.
4. The SERS substrate according to claim 2, characterized in that: The Ag@ZIF-8 solution was prepared by the following method: Zn(NO3)2·6H2O and dimethylimidazole were mixed and dissolved in solvent A, and AgNPs solution was added. The reaction was stirred and allowed to stand. The reaction solution was centrifuged and the precipitate was washed to obtain Ag@ZIF-8. Ag@ZIF-8 was dispersed in solvent B to obtain Ag@ZIF-8 solution.
5. The SERS substrate according to claim 4, characterized in that: The raw materials are selected from the following quantities: 100-300 parts of Zn(NO3)2·6H2O, 10-100 parts of dimethylimidazole, 50-100 parts of solvent A, 1-10 parts of AgNPs solution, and 1-10 parts of solvent B; wherein both solvent A and solvent B are methanol.
6. The SERS substrate according to claim 4, characterized in that: The stirring reaction conditions are selected from: stirring at 5-20° C. for 1-5 hours; and / or, the standing conditions are selected from: standing at 20-40° C. for 5-15 hours.
7. The SERS substrate according to claim 2, characterized in that: The AuNPs solution was prepared by the following method: Mix 0.25mL HAuCl4 and 7.5mL CTAB, then add 0.6mL ice-cold NaBH4 solution under magnetic stirring, and react for 1 minute to obtain a gold seed solution, which is stored at room temperature for 1 hour. The prepared gold seed solution is diluted 10 times for later use; 6.4mL CTAB solution is mixed with 0.8mL HAuCl4 solution, and 3.8mL AA solution, 32mL water and 20μL diluted gold seed solution are added in sequence; after standing for 4 hours, wash three times with ultrapure water by centrifugation, and then dissolve with 8mL methanol to obtain AuNPs solution.
8. Use of the Ag@ZIF-8@Au described in any one of claims 1 to 7 in the detection of diazepam residues.
9. A method for detecting diazepam residues in food, characterized in that: Here are the steps: 15 μL of Ag@ZIF-8@Au was transferred to the silicon wafer and dried naturally. Then, 15 μL of Ag@ZIF-8@Au was added to the silicon wafer again and waited for natural drying. 15 μL of the sample solution to be tested was added to the dried silicon wafer and placed in a vacuum drying oven at 60°C for 10 min. After drying, SERS detection was performed. If diazepam was present in the sample to be tested, the sample solution at 1076 cm -1 、1180cm -1 、1582cm -1 If diazepam does not exist in the sample to be tested, its Raman characteristic peak will not appear.
10. The detection method according to claim 9, characterized in that: The Raman parameters of the SERS detection were set as follows: laser wavelength of 532 nm, power of 3.1 MW, integration time of 0.01 s, 10 accumulations, and objective lens of 10×.